Contesting the Faith: Late 20th Century American Evangelicalism in Black and White. - Dorfman, Hannah J. (Tufts Archival Research Center, 2015)
Dominant stereotypes of American evangelical Christians as anti-intellectual, backward fundamentalists largely ignore the complex workings of race in the evangelical world. A more nuanced history of evangelical race relations is thus needed in order to highlight the intersection of race and religion in one of America’s most influential Protestant traditions. My project takes on this task by providing an in-depth look at the self-identified black evangelicals of the late 20th century. Their sermons, publications and organizations illuminate the diverse ways in which black Christians contested white norms and grappled with the very term “evangelical.” Some utilized secular Black Power ideology in the push for a separatist, black theology and worldview, while others advocated for a theology of racial reconciliation that engaged white Christians in an attempt to unite believers as one body of Christ. In uncovering this history, I argue that “evangelicalism” itself is a racialized term in that race dictated the very core of what it meant to be an evangelical Christian in the late 20th century.